Reconceptualization of Property in the Era of Digitalization: an Analysis of the Malaysian Anti-Fake News Bill 2018 - Wai Wong, Wai (International Journal of Engineering and Technology, 2018)
Fake news has dominated the social media. In response, the Malaysian Anti-Fake News Bill has been passed swiftly and it brought about awareness as well as other issues like the spread of unverified news and information. Clause 6 of the Bill imposes a duty on the person who is found in â€˜possessionâ€™ of fake news or such publication that contains fake news. However, the word â€˜possessionâ€™ is not defined. The objective of this paper is to critically examine the appropriate meaning of â€˜possessionâ€™ under Clause 6. News in the era of digitalisation is essentially made out of information and digital resources intangible, transferable, shareable and non-exhaustive.Â The notion of possession which derived from the traditional concept of property is not applicable to the unique nature of â€˜newsâ€™ in digital form. There is a need for a reconceptualization of property and the notion of â€˜possessionâ€™. Such new concept of property should not only describe â€˜propertyâ€™ as things but rather as â€˜rightsâ€™. The meaning of â€˜possessionâ€™ should refer to ownerâ€™s control, dominance and influence over news and information. This paper further examines how the new notion of possession ought to be applied in the context of Malaysian Anti-Fake News laws. Â Â